Wildlife trade in Brazil: A closer look at wild pets welfare issues - Kuhnen,VV (2014)
Wild animals have been kept as pets for centuries, in Brazil companionship is one of the main reasons why wild species are legally bred and traded. This paper is an attempt to call the attention for problems concerning the welfare of wild pets involved in the trading system in Brazil. Some issues presented are: a) the significant increase in the number of wildlife breeders and traders and the difficulties faced by of the Brazilian government in controlling this activity; b) the main welfare issues faced by breeders and owners of wild pets; and c) the destination of wild pets no longer wanted. Finally, some recommendations are made having the welfare of the animals as a priority.